Concepção de formação que fundamenta a integração entre ensino médio e educação profissional na Rede Pública Estadual do Maranhão - DUTRA, Nádya Christina Guimarães (2020)
This research proposes to analyze the concept of training that guides the Pedagogical Proposal of Maranhão's public schools of integrated high school, through the perception of managers, teachers and students. The research in question has the title “Conception of formation that bases the integration between High School and Professional Education in the State Public Network of Maranhão”, carried out within the scope of the Postgraduate Program in Education - Master's level, of the Federal University of Maranhão and falls within the line of research History, Educational Policies and Human Formation. As methodological procedures, bibliographic research was used to support the deepening of the research object and data analysis, notably with input from the writings of Karl Marx (2001), Antonio Gramsci (1981), Gaudêncio Frigotto (2005), Maria Ciavatta (2011), Otaíza Romanelli (2014), Dermeval Saviani (1994), Marise Ramos (2017), Acácia Kuenzer (2010), Jaqueline Moll (2010). Through documentary research, we find support in legislation, programs and proposals related to the object, such as Law No. 9,394 of 1996, Law No. 13,415 and Pedagogical Proposal for integrated schools in the public network of Maranhão. Through field research we seek to collect data using the following instruments: semi-structured interview applied together with school managers and teachers and questionnaire to students in the first and third grades of high school. Thus, it discusses the concepts that underlie the integration between high school and professional education in Brazil, as well as the relationship between work and education and the concept of comprehensive training. The results of the analyzes on the understanding of managers, teachers and students in relation to the Pedagogical Proposal of integrated high school experienced in the empirical field are presented. We conclude that the concept of integration that guides the operational model does not have an organic relationship with pedagogical practices, establishing an understanding where training for the world of work is an alternative within the curriculum and not the basis for the promotion of comprehensive training that is objective in the teaching proposal.